*Fan & Medal*
Please explain how I can do this, I want to learn it.
Let f(x) = -2x + 4 and g(x) = -6x - 7. Find f(x) - g(x)

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

HI... I can help you

Okay... How do I solve this?

Hmm... you should find f(x)-g(x)=(-2x+4)-(-6x-7)=-2x+6x+4+7=4x-11

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.